How do firms organize trade?: Evidence from Ghana - Jens Krüger (Kiel Institute for the World Economy (IfW), 2009)
The literature on firm heterogeneity in international trade posits that only the most productive firms become exporters (Melitz 2003). However, empirical findings suggest that also firms that are not highly productive export. This paper investigates empirically how firms organize their export trade. If selling directly, sunk costs of foreign market entry are arguably very high, so only productive firms can achieve this (Schroeder et al. 2003). Low productivity firms, by contrast, may prefer to export through trading companies, which involves lower sunk costs. Using a firm level panel data set of Ghanaian firms we investigate the relationship between firm productivity and the use of export intermediaries. Our estimation results take simultaneity problems into account and reveal that indeed low productivity firms tend to export through intermediaries.
Keywords: D21; F14; L22; 330; Export intermediation; firm productivity; Außenhandelswirtschaft; Unternehmen; Produktivität; Exporthandel; Internationale Markteintrittsstrategie; Ghana